2020
DOI: 10.1139/cjfas-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Out with the old and in with the new: T90 codends improve size selectivity in the Canadian redfish (Sebastes mentella) trawl fishery

Abstract: The size selectivity of four codends were compared in the Gulf of St. Lawrence, Canada redfish fishery, including the regulated diamond mesh codend with a mesh opening of 90 mm (T0) and three experimental codends of different mesh openings (90, 100, 110 mm) in which the netting is turned 90° to the direction of tow (T90). Results for the regulated codend showed that there was little size selection, catching greater than 97% of redfish over all of the length classes observed. Considering the fished population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Netting meshes can change their physical properties over time, which can lead to that selectivity devices constructed of netting meshes lose their selection properties. Squaremeshed panels (e.g., the BACOMA codend (Herrmann et al 2015;Madsen et al 2015), codends with lateral exit windows (Grimaldo et al 2008;Grimaldo et al 2009), andT90 codends (ICES 2011;Madsen et al 2015;Cheng et al 2020)) have good selection properties for cod and haddock. However, deformation of the meshes and loss of stiffness over time may change the selection properties of these types of codends.…”
mentioning
confidence: 99%
“…Netting meshes can change their physical properties over time, which can lead to that selectivity devices constructed of netting meshes lose their selection properties. Squaremeshed panels (e.g., the BACOMA codend (Herrmann et al 2015;Madsen et al 2015), codends with lateral exit windows (Grimaldo et al 2008;Grimaldo et al 2009), andT90 codends (ICES 2011;Madsen et al 2015;Cheng et al 2020)) have good selection properties for cod and haddock. However, deformation of the meshes and loss of stiffness over time may change the selection properties of these types of codends.…”
mentioning
confidence: 99%
“…The 110 mm T90 codend would catch 50% less redfish below MLS but lose 40% of redfish above MLS. Overall, the results showed that T90 codends improve size selectivity in which large proportions of undersized fish can be successfully released (Cheng et al 2020).…”
Section: Fish Capturementioning
confidence: 88%
“…They compared the size selectivity of four codends in Unit 1, including the regulated diamond mesh codend with a mesh opening of 90 mm (T0) and three experimental codends of different mesh openings (90, 100, 110 mm) in which the netting was turned 90 • to the direction of tow (referred to as T90). Results for the regulated codend showed that there was little size selection, catching greater than 97% of redfish over all the length classes observed (Cheng et al 2020). Considering the fished population, the smallest T90 codend would catch 30% fewer redfish under the minimum landing size (MLS) of For personal use only.…”
Section: Fish Capturementioning
confidence: 97%
See 1 more Smart Citation
“…This study sought to alleviate the consequences that arise in deep-water shrimp fisheries as a result of insufficient codend mesh openings (Cheng et al 2020). In order to increase codend mesh openness and thus enabling an increase in escape of deep-water shrimp below the MS and juvenile fish, two approaches were taken.…”
mentioning
confidence: 99%